The Effectiveness of a Nondiet Multidisciplinary Weight Reduction Program for Severe Overweight Patients with Psychological Comorbidities - Bettina Bannert; Wolfgang Schobersberger; Ulrich Tran; Andreas Remmel (Journal of Obesity)
Objective. For successful sustainable weight reduction, a multimodal program including behaviour therapy is needed. Lifestyle modification is mostly used for obesity BMI <40 kg/m2. The present study demonstrated the effect of an in-patient nondiet lifestyle program for patients with BMI >40 kg/m2 with psychological comorbidity. Research Methods and Procedere. A retrospective data analysis of 99 participants who passed the program based on moderate activity, healthy and regular food intake over metabolic rate and behaviour therapy was conducted. Results. 64 had a BMI >40 kg/m2 (mean value 49.99±8.74). The relative weight reduction was −6.9 ± 3.9%; (Friedman test P<0.05). Binary logistic regression analysis for n=79 revealed that the achievement of the weight reduction goal (0.5 kg per week; predictors: sex, incidence of MTS, duration of in-patient therapy, psychological symptoms, BMI and activity level at baseline) was associated with a shorter duration of in-patient therapy (P=0.007) and higher BMI at baseline (P=0.010). Conclusion. Participants with BMI >40 kg/m2 may achieve significant changes of weight reduction and psychological symptoms. However, the primary outcome should not be weight reduction. It is necessary to identify the benefits of lifestyle modification on changing risk profiles and emotional regulation of food intake.